Implementation of the Multiple Representation Based of Investigation Learning Model Aided by Virtual Replica on Direct Current Pathway Material to Improve Cognitive Learning Outcomes of High School Students - Wiwi Ruyal Aini; Dedi Irawan; Muhammad Nasir (FKIP - Universitas Riau, 2026)
This research aims to describe and determine the cognitive learning outcomes of students who apply Multiple Representation Based of Investigation learning model aided by virtual replica for class XII students. This research used a quasi-experimental design with a post-test only group. This research was conducted at Madrasah Aliyah (MA) Darul Hikmah Pekanbaru with a population of 79 students. The research instrument used was a post-test of learning outcomes with cognitive aspects, with 20 multiple-choice questions. The results of descriptive analysis show that the cognitive learning outcomes of students who learn with the Multiple Representation Based of Investigation learning model aided by virtual replica achieved an average score of 80.04 (Good Category). The results of the inferential analysis using the t-test sample obtained a 2-tailed sig value of 0.000, with a 95% confidence level. This research shows that the Multiple Representation Based of Investigation learning model aided by virtual replica can improve students' cognitive learning outcomes in direct current pathway material, providing alternative teaching strategies that can improve students' cognitive learning outcomes.